Innovative Forms of Financing the Creation and Development of Small Business - Yermak Svitlana O.; Kostakova Lina D.; Plotnitskaya Veronika V. (Problemi Ekonomiki, 2017)
For small enterprises, unlike large ones, the issue of fundraising emerges both in the process of their creation, development and current activity. Small enterprises are experiencing quite a high demand for additional sources of financing. The aim of the research is to study innovative forms of financing the creation and development of small enterprises, their advantages and disadvantages. At present in addition to traditional ways of raising capital, such as bank loans or public offering of shares among external investors (IPOs), there exist a number of alternative options. Among them the most common are grants, international programs, loans from international banks and financial institutions, such as EBRD (European Bank for Reconstruction and Development), IFC (International Finance Corporation), NEFCO (Nordic Environment Finance Corporation), KfW (Kreditanstalt f?r Wiederaufbau), fundraising, crowdsourcing, crowdfunding, and angel investment. The article studies in detail the last two ways of financing: their essence, components, positive and negative features, experience of application in Ukraine and the world. The research shows that crowdfunding is suitable for business development at the early stages, that is, for those enterprises that require, for example, to complete prototyping and start mass production of their first product. Business angels can be a good choice for enterprises that already have a permanent customer base and want to grow their business.